The relationship between intercultural effectiveness and intercultural awareness and xenophobia among undergraduate nursing and vocational schools of health services students: A descriptive study. (December 2021) - Gungor, Serap; Tosun, Betul; Prosen, Mirko
Abstract: Background: Students who will become health professionals should be educated according to universal standards of providing foreign patients with culturally satisfying health care, free from discrimination. Aim: This study aims to identify the relationship of intercultural effectiveness and awareness with xenophobia in undergraduate nursing students and vocational schools of health services students. Method: This descriptive study was conducted with undergraduate nursing students ( N = 257) and vocational schools of health services students ( N  = 341) in a region with a high refugee population in Turkey. Data were collected through the "Intercultural Awareness Scale, " the "Intercultural Effectiveness Scale, " and the "Xenophobia Scale." Results: Of all the participants, 70.1% were females, and the mean age was 20.70 ± 2.64 years; 57% of the students were from the vocational school students, and 43% from the undergraduate nursing program. Female students had significantly higher scores in intercultural effectiveness, behavioral flexibility, xenophobia ( p  = 0.036, p  = 0.041, p  = 0.001, respectively), interaction relaxation and interactant respect ( p  < 0.001, p < 0.001), while male students had significantly higher intercultural awareness (p < 0.001). The median intercultural effectiveness score of the students living in the rural area was low ( p  = 0.044), and the median xenophobia score of the students who lived abroad was significantly lower ( p  = 0.032). There was a negative correlation between the Intercultural Effectiveness Scale total and Intercultural Awareness and Xenophobia Scale total mean scores (r = -0.085, r  = 0.182), and there was a weak, positive correlation between the Intercultural Awareness Scale total mean scores and the Xenophobia Scale mean scores ( r  = 0.113). Conclusion: Intercultural sensitivity is considered to be improved by including course content in the curriculum to improve students' intercultural effectiveness and awareness levels and decrease their xenophobic prejudices. Highlights: Healthcare professionals should be educated about the cultural characteristics of the patients. Results showed that the nursing students and vocational students had high level of xenophobia. The results highlighted the need for effective education programs for intercultural health care. While the intercultural awareness perception was increasing, xenophobia was decreasing.